THE EFFECT OF GIVING MUNG BEAN EXTRACT ON BREAST MILK PRODUCTION IN POST-PART MOTHERS IN DEPOK CITY, WEST JAVA - Silfia Nuzulus Sa’idah; Lusy Pratiwi; Desy Qomarasari; Daris Yolanda Sari; Ruci’ah (PT. Radja Intercontinental Publishing, 2026)
Introduction: Breast milk is the best source of nutrition for infants; However, suboptimal breast milk production during the postpartum period remains one of the barriers to successful exclusive breastfeeding. Mung bean (Vigna radiata), as a local food rich in protein, vitamins, and minerals, has the potential to be used as a non-pharmacological intervention to support increased breast milk production. This study aimed to analyze the effect of consuming 250 ml mung bean extract on breast milk production among postpartum mothers. Methods: This study used a quasi-experimental design with a pretest-posttest approach. The sample consisted of 36 postpartum mothers who received 250 ml of mung bean extract once daily for 7 days. Data were collected using a breast milk production observation checklist and analyzed using the paired t-test. Results: Before the intervention, most respondents had low breast milk production (18 respondents; 50.00%), followed by moderate production (11 respondents; 30.55%) and good production (7 respondents; 19.45%). After the intervention, breast milk production improved, with 21 respondents (58.33%) categorized as good, 8 respondents (22.22%) as moderate, and 7 respondents (19.45%) as low. The paired t-test showed a significant difference in breast milk production before and after mung bean extract administration (p-value = 0.001; p < 0.05). Conclusion: Consumption of 250 ml mung bean extract significantly increased breast milk production among postpartum mothers. Mung bean extract can be considered an effective, safe, and affordable local food-based non-pharmacological intervention to support exclusive breastfeeding success.